2009
DOI: 10.1111/j.1365-2648.2009.05114.x
|View full text |Cite
|
Sign up to set email alerts
|

Reporting behaviours of nursing students who have experienced verbal abuse

Abstract: Failure to document experiences of verbal abuse formally was prevalent and reporting practices were variable. Both higher education institutions and healthcare providers should consider establishing process for formal reporting and documenting of incidents of verbal abuse during nurse education, and students should have access to formal support services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 43 publications
3
35
2
2
Order By: Relevance
“…In similar studies on the subject, the majority of nursing students in clinical areas were identified as having been exposed to verbal violence (Arslantaş et al, 2012;Çelebioğlu et al, 2010;Çelik & Bayraktar, 2004;Ergöl & Kürtüncü, 2013;Ferns & Meerabeau, 2009;Hinchberger, 2009;Lash et al 2006;Özcan et al, 2014;Ünal et al, 2012). Our research results are similar to the results of previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…In similar studies on the subject, the majority of nursing students in clinical areas were identified as having been exposed to verbal violence (Arslantaş et al, 2012;Çelebioğlu et al, 2010;Çelik & Bayraktar, 2004;Ergöl & Kürtüncü, 2013;Ferns & Meerabeau, 2009;Hinchberger, 2009;Lash et al 2006;Özcan et al, 2014;Ünal et al, 2012). Our research results are similar to the results of previous studies.…”
Section: Discussionsupporting
confidence: 83%
“…Nurses were an oppressed group in male-dominant occupational environments so they tended to dissolve their own suffering associated with their powerlessness through bullying young coworkers or subordinates [26]. In the same way, nursing students came to become a target of bullying because of lack of professional experience and ability to deal with conflicts in clinical settings [4,8,25]. Also, nursing students were likely to assimilate bullying into their nursing practice as they were silent about this painful experience [25].…”
Section: Discussionmentioning
confidence: 99%
“…From the hierarchical culture-based perspective of healthcare professions, nursing students are prone to become a target group of be-ing bullied [4] because their status seem to be lower than junior nurses in this cultural context. It was suggested that lack of clinical experience and frequent ward changes were also associated with a decreased sense of control to adapt unfamiliar clinical environment and subsequent powerlessness, possibly leading to increased vulnerability to bullying in nursing students [8]. Due to a high risk of being bullied in clinical placement, nursing students may not be able to have a successful transition period from undergraduate students to healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, further evidence suggested a significant underreporting of verbal abuse, which the authors contributed to students reporting a lack of action or feedback provided, an increase in negative feelings and evidence of bullying toward them, and a lack of support following reporting. 28 Hinchberger 29 distributed an online survey on violence against nursing students in the workplace, which examined 126 participants' responses and found that all had either observed or experienced violence in the clinical setting. The majority of perpetrators were staff members (50%), followed by patients (25%).…”
Section: Prevalence Ratesmentioning
confidence: 99%